Load-deflection behaviour of concrete slab-type elements casted on stay-in-place TRC formwork. (15th July 2020) - Kim, Hyeong-Yeol; Koh, Kyung-Taek; You, Young-Jun; Ryu, Gum-Sung; Seo, Dong-Woo; Jin, Seung-Seop; Ahn, Gi-Hong; Nam, Jeong-Hee
Abstract: This paper presents the design and experimental validation of a durable textile reinforced concrete (TRC) panel that can be used to furnish a stay-in-place (SIP) formwork and a protective layer over the outer surface of the reinforced concrete (RC) elements, which require high durability and long service life. The objectives of this study are to increase the flexural capacity and to improve the durability of the RC elements by employing an SIP TRC formwork panel. A durable binder system was designed to offer excellent durability performance in a chloride-rich environment. Six full-scale RC slab-type specimens were casted on the SIP TRC formwork. The load-deflection behaviour of the full-scale slab specimens was compared with the analytical solutions. The results of a full-scale flexural failure test indicated that the ultimate flexural capacity of the slab specimens with the TRC formwork was at least 141% greater than that of the RC slab without the TRC formwork.